Article of KDBK in English 20 The Advancement of Demographics Learning Tools: The Advancement of Demographics Learning Tools - Siagian, Pargaulan (Advances in Social Sciences Research Journal, 2020)
This study is aimed at producing a learning tools to a lecturing program in form of : lectures unit (SAP), Lecturing Text Books (BTPM), and Demography lecturing attendant activity sheet (LKPDM), and the ability assessment of attendant program (PKHPM) it is all in order to ensure demography subject be more valid, practical, and effective with in a learning model aided with Think, Pair and Share (TPS) and data based. The teaching material matter to Demography Techniques subject to develop such as; Introduction, base source of statistics, collecting and data processing of demographic, size population, population distribution of geographic region, population distribution of geographic area, the age composition and gender, composition of race and ethnic, change of population, education and characteristics of economic, mortality, life table, demography of health, birth-rate bases to census and survey, population growth, international migration, internal migration and short-time mobility, and population forecast. The process how to implement perhaps prepare an attending tools component either : to plan an attendant unit (SAP), attendance book of demographic (BBKD), and attendance activity sheet (LKPM), and ability test of Demographic study (TKHPD), and ability assessment of attendant program (PKHPM) to be distributed over all Lecturers Team on Mathematics Department of FMIPA Unimed.